Performance Evaluation of Significant Intersections (Apill Adaptive Radar and Loop Detector) - Nurul Fitriani; Edi Purwanto; Moh. Rifki Tsani; Budi Mardikawati; Dwi Wahyu Hidayat (Jurnal Teknologi Transportasi dan Logistik, 2022)
The size of the performance of the intersection can be determined based on the length of the queue, the number of vehicles stopped, and the delay. To minimize delays at signalized intersections, it is necessary to adjust each phase's cycle time and green time according to the traffic flow. Adaptive APILL is considered the answer to that. In Tegal City, two adaptive APILL have been installed: the adaptive radar APILL and the loop detector adaptive APILL. However, the performance of the adaptive APILL that is already installed is not known with certainty. Therefore, the researcher conducted a study to determine the performance of each existing adaptive APILL. The research was conducted as an experiment by treating the cycle time setting at the adaptive APILL intersection, namely when the adaptive APILL is on and the adaptive APILL is off. VISSIM and SSAM are used to analyze the performance of intersections and conflicts. From the results of the analysis, it can be concluded that 1) The performance of the intersection is less than optimal when adaptive radar APILL at Intersection 4 Alun-Alun Tegal on 2) The performance of the intersection is more optimal when loop detector adaptive APILL is at Simpang 4 Hang Tegal on.